Suppression of interference in spread-spectrum systems using signal processing techniques - Kot, Alex Chichung. (2008)
Proposed a fast fourier transform based signal processing algorithm to combat the intentional partial band jamming for three different types of receivers, namley clipper receiver, self-normalizing receiver and product combining receivers.